2017
DOI: 10.1111/1471-3802.12379
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy of prospective Austrian and German primary school teachers regarding the implementation of inclusive education

Abstract: This study examined the psychometric properties of the German version of the Teacher Inclusive Education Self‐Efficacy Scale (TIESES). Five hundred and nineteen teacher education students from Austria and 765 teacher education students from Germany participated in the study. Results of a multiple‐group confirmatory factor analysis (for the two countries) confirmed a single factor structure of the scale with partial scalar measurement invariance. Regression analysis showed that self‐efficacy when implementing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 49 publications
1
24
1
6
Order By: Relevance
“…However, as Hornby (2015) argue, the main point would be not merely to involve SEN students in mainstream classes, but to design special curricula for children with SEN, which are more appropriate for them with requirements adjusted to their needs. Most other European studies reported such trends (Chitiyo and Brinda, 2018;Schwab et al, 2017;Seçer, 2010). However, the lowest means were recorded in teachers' competences.…”
Section: Discussionmentioning
confidence: 75%
“…However, as Hornby (2015) argue, the main point would be not merely to involve SEN students in mainstream classes, but to design special curricula for children with SEN, which are more appropriate for them with requirements adjusted to their needs. Most other European studies reported such trends (Chitiyo and Brinda, 2018;Schwab et al, 2017;Seçer, 2010). However, the lowest means were recorded in teachers' competences.…”
Section: Discussionmentioning
confidence: 75%
“…Pre-service teachers enrolled in an intensive training in disabilities and inclusion as well as those with extensive experience with students with SEN had significantly higher self-efficacy scores than the group with minimal training and experience (Leyser, Zeiger, and Romi 2011). Other factors also correlated with their self-efficacy for inclusion, including frequency and intensity of contact with people with disabilities (r = .09), the number of semesters of study (r = −.19) and prospective teachers' motivation for working in inclusive education (r = .38) (Schwab, Hellmich, and Görel 2017). Moreover, Hellmich and Görel (2014) found significant relationships between experienced primary teachers' self-efficacy and their attitudes towards inclusion (r = .53) as well as between teachers' self-efficacy and their motivation to deal with inclusive education (r = .49).…”
Section: Factors Associated With Self-efficacy For Inclusive Educationmentioning
confidence: 99%
“…Dapatan kajian lepas telah menjadikan faktor demografi seperti jantina dan pengalaman mengajar faktor penentu kepada peningkatan efikasi kendiri. Misalnya, perbezaan pengalaman mengajar dengan efikasi kendiri (Schwab, Hellmich, & Görel, 2017;Yada, Tolvanen, & Savolainen, 2018) iaitu kurang pengalaman mengajar lebih mencabar untuk mengurus tingkah laku MBK (Monteiro et al, 2018). Namun kajian Kuyini et al, 2018 sedikit berbeza dengan dapatan yang lain iaitu umur dan pengalaman mengajar tidak mempengaruhi efikasi kendiri guru perdana.…”
Section: Pengenalanunclassified